(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2025)
This paper examines the English vowel phoneme system, analyzing their distinctive phonological features (height, backness, roundness) and organization within the language. It provides a comprehensive study of vowel distribution patterns across different linguistic contexts, including dialect variations and stress effects. The paper combines both acoustic and articulatory data to improve our understanding of English vowel phonology, with applications for language teaching and learning.